Transformation of fracture mode of an Al-Mg-Si-Cu alloy subject to aging treatment - Gao, Lin; Zhang, Lixin; Gu, Ji; Ou, Xiaoqin; Ni, Song; Li, Kai; Du, Yong; Song, Min (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2018)
In this work, the microstructure of Al-Mg-Si-Cu alloy was tailored by controlling the aging process and its effect on the fracture mechanism was systematically explored by in-situ tensile test and microstructural observations. It was found that the aging process influences the mechanical performance and leads to the alteration of the tensile fracture mode of the aged alloy. Microscopy observations revealed that the Al2Cu precipitates distribute heterogeneously in the peak-aged alloy. The density of the Al2Cu precipitates in the intergranular fracture regions is much higher than that in the transgranular regions. The effect of Al2Cu precipitates on the fracture mode was systematically discussed and a hybrid fracture mechanism was proposed.